G.I. Jane - Scott, Ridley; Twohy, David; Alexandra, Danielle; Moore, Demi.; Mortensen, Viggo, 1958-; Bancroft, Anne, 1931-2005.; Beghe, Jason; Wilson, Scott, 1942-; Jones, Trevor, 1949-; Hollywood Pictures; Caravan Pictures; Largo Entertainment (Firm); et al. (Calif.] Hollywood Pictures Home Video Distributed by Buena Vista Home Entertainment, 1998)
Lieutenant O'Neil is the first woman ever given the opportunity to earn a place in the armed forces' most highly skilled combat unit--the elite Navy SEALs. But the already brutal rigors of training camp turn into an unimaginable test of courage and determination once it becomes clear that no one--powerful politicians, top military brass or her male Navy SEAL teammates--wants her to succeed.
Originally released as a motion picture in 1997.
Special features include; theatrical trailer, scene selections.
Music, Trevor Jones ; editor, Pietro Scalia ; director of photography, Hugh Johnson ; co-producer, Nigel Wooll ; producers, Roger Birnbaum, Demi Moore, Suzanne Todd ; screenplay, David Twohy, Danielle Alexandria ; producer/director, Ridley Scott.
Demi Moore, Viggo Mortensen, Anne Bancroft, Jason Beghe, Scott Wilson.
DVD format, Dolby ditital, digital sound, widescreen format (aspect ratio 2.35:1)
English or French language with optional subtitles in Spanish ; English closed-captioned for the hearing impaired.
Keywords: United States -- Navy -- SEALs -- Drama; Women sailors -- Drama; Feature films -- United States; Films for the hearing impaired